PENGELOLAAN UJIAN NASIONAL SEKOLAH STUDI KASUS DI SMP NEGERI 1 SUKOLILO PATI - MASTURI, MASTURI (2011)
The National Exam is used as one consideration for (a) the mapping of quality educational programs and or units (b) the basis of selection into the next education level, (c) determining the graduation of students from the educational unit, and (d) developing and providing assistance to the educational unit in an effort to improve the quality of education. The successful implementation of the national exam is determined by the role of one of the school. Schools have an important role in designing a specific strategy to be followed and implemented. Among the strategies relating to the schedule of additional material, implementation of additional learning material, and the holding of national examinations. This type of research is qualitative or naturalistic research focusing characteristics of the management of national examinations and school schedule sub focus of research characteristics of learning materials, additional material characteristics of the activities and characteristics of the implementation of the national exam. Data collection techniques used are in-depth interviews, observation, and documentation. The collected data were analyzed through three main activities are interrelated and occur simultaneously, namely data reduction, data presentation, and conclusion or verification. The results showed that characteristics of the schedule for additional provision of learning materials designed national examinations at grade IX semester one and semester two. The design includes the addition of the number of hours of lessons, design activities surgical competency standards national exam, and socialization to parents / guardians of students. Characteristics provision of additional learning materials in SMP Negeri 1 Pati Sukolilo, ie additional materials lesson for grade IX students is subject Indonesian Language, Mathematics, English, and Natural Sciences, additional material in the form of deepening learning subject matter in accordance with the standards of competence lukusan ( SKL) national exam, measuring the success of additional course material through solving exercises questions predicted a national exam in accordance with the SKL-National, and try out / test a national exam. Characteristics of the implementation of the national exam that is the data collection and registration of candidates for national examinations, the formation of executive committee of national examinations, preparation of work plan implementation of the national exam, preparing the implementation of the national exam guidelines, determining the criteria for graduation, the conduct of national examinations, issuance of diplomas and reporting the implementation of the national exam.